2008
DOI: 10.1016/j.bbalip.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the roles of sphingosine 1-phosphate and its type 1 G protein-coupled receptor in T cell immunity and autoimmunity

Abstract: The lipid mediator sphingosine 1-phosphate (S1P) and its type 1 G protein-coupled receptor (S1P 1 ) affect mammalian immunity through alterations in thymocyte emigration, differentiation of T cell subsets, lymphocyte trafficking in lymphoid organs and other tissues, T cell-dendritic cell and T cell-B cell interactions, and cytokine generation. Recent attention to effects of the S1P-S1P 1 axis on nonmigration functions of lymphocytes include delineation of a role in terminal differentiation and survival of Th17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…The underlying mechanism strongly suggests that T‐cell function is altered by FTY720, suppressing Th2 differentiation. Others have suggested that FTY720 supports the induction of Tregs To establish a better insight into how local FTY720 modulates the immune response, we studied its effect on T‐cell proliferation and Th differentiation in vitro and in vivo . T‐cell proliferation was inhibited in vivo in the NALT structures but not in the cervical nodes, due to the topical i.n.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism strongly suggests that T‐cell function is altered by FTY720, suppressing Th2 differentiation. Others have suggested that FTY720 supports the induction of Tregs To establish a better insight into how local FTY720 modulates the immune response, we studied its effect on T‐cell proliferation and Th differentiation in vitro and in vivo . T‐cell proliferation was inhibited in vivo in the NALT structures but not in the cervical nodes, due to the topical i.n.…”
Section: Discussionmentioning
confidence: 99%
“…S1P exerts its action by binding to five structurally related G-protein-coupled receptors (S1P1–S1P5 receptors) [52] . Because S1P sequesters lymphocytes and inhibits T-cell chemotaxis and T-cell proliferation [53] , the S1P agonist FTY720 is proposed to treat transplant rejection and autoimmune disease such as multiple sclerosis [54,55] . Besides, FTY720 has a protective effect on ischemia-reperfusion animal models and improved diabetic kidney injury without alterations of T and B cells [56,57] .…”
Section: Nonimmunologic Targets Of Immunosuppressive Agents In Podocymentioning
confidence: 99%
“…Early studies implicated S1P and S1PR1 in regulating the differentiation of Th2, Treg, and Th17 cells, while limiting Th1 cells (Goetzl et al, 2008). More recent studies have demonstrated that S1PR1 restrains thymic development of Tregs, their peripheral numbers and their suppressive functions (Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%